An Electroactive and Transparent Haptic Interface Utilizing Soft Elastomer Actuators with Silver Nanowire Electrodes. Issue 35 (30th July 2018) - Jun, Kiwoo; Kim, Jongnam; Oh, Il‐Kwon
Abstract: An electroactive and transparent haptic interface having a rectangular void pattern creates tunable surface textures by controlling the wavelength and amplitude of independent void‐lines. To make an active tactile surface, the transparent haptic interface employs a silver nanowire (AgNW) electrode to be compliant with the deformed elastomer surface. Here, the dielectric elastomer is newly blended with polydimethylsiloxane and Ecoflex prepolymer to simultaneously control the mechanical stiffness and transparency. The relative resistance of the AgNW electrode on a single void line is nearly unchanged under bending test, confirming the high stretchability and conductivity of the nanowire‐networked electrode. The optical transparencies are 92–85%, depending on the ratio of the Ecoflex solution. Transparency values decreas by 7 and 16% after coating with AgNWs at densities of 30 and 140 mg m −2, respectively. Using EP31, the void line is deformed by 90 µm under a field intensity of 13.0 V µm −1 . The haptic surface is successfully controlled by applying voltage, which produces four different surface textures, from relatively smooth to rough feeling, depending on the distance between deformed void lines. This haptic interface can be applied to diverse display systems as an external add‐on screen and will help to realize programmable surface textures in the future. Abstract : An electroactive and transparent haptic interface with a periodically arranged rectangular void pattern is developed by utilizing blended soft elastomers and a stretchable silver nanowire electrode. The resulting haptic interface can be used to produce various surface textures via active control of individual void lines, suggesting its potential applications in versatile display systems as an external add‐on screen.